2017
DOI: 10.1111/1556-4029.13347
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Composition and Pulmonary Surfactant Protein Expression as Markers of Death by Drowning

Abstract: Pathological diagnosis of drowning remains a challenge for forensic science, because of a lack of pathognomonic findings. We analyzed microbiota and surfactant protein in the lungs for a novel diagnosis of drowning. All rats were divided into drowning, postmortem submersion, and control groups. The water, lungs, closed organs (kidney and liver), and cardiac blood in rats were assayed by targeting 16S ribosomal RNA of Miseq sequencing. Lung samples were analyzed by immunohistochemical staining for surfactant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The findings revealed that the microbial community in the closed organs was a significant marker for the diagnosis of death by drowning. Likewise, the same study hypothesized that drowning is associated with higher expression levels of surfactant protein A (regarded as a valuable marker of asphyxiation and acute lung injury) in the lung of true drowning victims (Lee et al 2017).…”
Section: Drowning Casesmentioning
confidence: 98%
See 3 more Smart Citations
“…The findings revealed that the microbial community in the closed organs was a significant marker for the diagnosis of death by drowning. Likewise, the same study hypothesized that drowning is associated with higher expression levels of surfactant protein A (regarded as a valuable marker of asphyxiation and acute lung injury) in the lung of true drowning victims (Lee et al 2017).…”
Section: Drowning Casesmentioning
confidence: 98%
“…The diatoms' presence in blood or organs (e.g., lungs, kidneys, spleen, liver and bone marrow) from the victims has been frequently considered as the gold standard indicator for drowning cases, discriminating between antemortem immersion (live entry) and postmortem submersion (dumping of a dead body) or even indicating the location of a probable drowning place (seawater vs. freshwater diatoms) (Sitthiwong et al 2014;Spitz and Schneider 1964). However, this analysis presents several constraints: (i) diatoms may be present in low concentrations in some water sources, being difficult to detect even in some true drowning victims; (ii) some of these microorganisms present relatively large diameter/length (ranging between 2 and 500 μm), limiting their transposition of the alveolar wall and, consequently, their passage into the blood stream and organs; (iii) diatoms can be disclosed in several organs (e.g., kidney, liver and lungs) of nondrowned bodies (Calder 1984;Kakizaki et al 2010;Kakizaki et al 2009;Lee et al 2017).…”
Section: Drowning Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kakizaki et al (2012) used the 454 pyrosequencing approach to ascertain the cause of death of two drowning cases and found that it is possible to determine diverse aquatic microbes in drowning victims that can point toward the aquatic environment in which the drowning occurred. An animal study sampled for lungs, kidney, liver, and blood, and found significant aquatic microbial presence in the drowned group compared to closed organs of postmortem immersion group (Lee et al, 2017). Aquatic bacterial communities were further dominated by Proteobacteria (seawater), Bacteroidetes (freshwater), Actinobacteria, and Bacillariophyta (Lee et al, 2017).…”
Section: In Drowningmentioning
confidence: 99%